TINGKAT KEPUASAN PETANI MITRA KENTANG TERHADAP KINERJA KEMITRAAN DENGAN CV. BUMI AGRO TECHNOLOGY (Suatu Kasus Petani Kabupaten Garut) - Azahra, Shabrina Puti; Tridakusumah, Ahmad Choibar; Karyani, Tuti; Sadeli, Agriani Hermita (Universitas Galuh, 2023)
Partnership can be one of the efforts to overcome problems that are often faced by horticultural farmers such as price, marketing, input provision, and capital availability. This study aims to explain the characteristics of farmers who partner with CV. Bumi Agro Technology, explaining the pattern of partnerships implemented, analyzes the satisfaction of partner farmers in partnering. This research is quantitative and qualitative research (mix method) using customer satisfaction index (CSI) and importance performance analysis (IPA) data analysis tools. This study was conducted in Garut Regency, West Java Province on 29 farmer respondents who were determined using the census sampling method. The results of the study are as follows: partnership pattern used by CV. Bumi Agro Technology and partner farmers are Agribusiness Operational Cooperation (KOA), the level of satisfaction of partner farmers with partnership performance is seen from five variables including satisfaction with the CSI value of 79.71%, attributes that are the top priorities to improve are policy attributes for partnership, quality of potatoes produced, accuracy of seed quality, improvement of farmer insight, guidance.